QuillBot Use in Student Writing: A Technology Acceptance Model Analysis - Devian Try Gustary; Silvia Putri Anjani; Anggit Laesa Oktaviani (Universitas Mulawarman, 2025)
The purpose of this study is to determine the extent to which the use of Quillbot, an artificial intelligence-based writing tool, influences students' academic writing skills. This study examines the experiences, perceptions, and impact of Quillbot use on the quality of students' writing, employing a mixed-methods approach. The research respondents were students who actively used Quillbot to complete various academic tasks, such as essays and research reports. The results of the study indicate that students consider Quillbot to be a useful tool for enhancing the clarity and neatness of their writing, as well as correcting grammatical errors. The main indicators of the Technology Acceptance Model (TAM), Perceived Usefulness and Perceived Ease of Use, indicate positive perceptions of technology use and encourage its continued use. This study confirms that perceived utility and perceived ease of use have a considerable impact on students’ attitudes and behavioural intentions, supporting the theoretical assumptions of TAM. In addition to being a technological tool, QuillBot serves as a teaching tool that encourages students' self-assurance and independence in academic writing.